Pertumbuhan Ekonomi dan Ketimpangan Pendapatan Antar Kabupaten/Kota di Provinsi Kalimantan Selatan Tahun 2010-2017 - Alfian Noor Rahman; Muhammad Handry Imansyah (PPJP Universitas Lambung Mangkurat, 2021)
This study aims to analyze the validity of the Kuznets hypothesis in South Kalimantan Province during the period 2010-2017. Data analysis method used in this study is to use quadratic regression analysis using the Ordinary Least Square (OLS) method that uses cross section data in 13 districts / cities in South Kalimantan Province in 2010-2017. The analysis in this study was carried out with the help of E-views 9 software. The results in this study indicate that in 2010, 2014 and 2015 the Kuznets hypothesis applies in South Kalimantan while in 2011, 2012, 2013, 2016, 2017, and overall from 2010-2017 the Kuznets hypothesis does not apply in South Kalimantan. Even in 2012 it tends to draw slashes increasing right. And for the other years, it depicts U-shaped curves. Based on the regression results it was found that in 2010 to 2016 and overall in 2010-2017 the data showed no significant effect while the data in 2017 showed a significant effect.